Peran Sumber Daya Manusia dalam Memoderasi: Pengaruh Standar Akuntansi Pemerintahan dan Pengendalian Internal terhadap Kualitas Laporan Keuangan Pemerintah Desa - Akbar Agustian; Bestari Dwi Handayani (SENTRI: Jurnal Riset Ilmiah, 2025)
his study aims to analyze and understand the extent to which the Government Accounting Standards System (SAP) and internal control affect the quality of village government financial reports, as well as to determine the role of human resources (HR) in moderating the relationship between these variables. This research employs a quantitative approach with an associative research type. The study was conducted in village governments within the Central Java Regency area. The population in this study consists of village government officials directly involved in the village financial management process, such as financial staff, planning officers, village heads, and village secretaries. This study identifies a gap in the literature regarding how the role of Human Resources (HR) can influence the effectiveness of the implementation of these two factors in the context of village government. The selection of HR as a moderator variable is based on a theoretical approach that emphasizes the importance of individual competence and motivation in carrying out accounting and internal control functions. The data collection method was carried out by distributing questionnaires to 36 respondents in the field, consisting of 30 statement items using a Likert scale. Statistical data analysis was performed using Jamovi Software version 2.5.6. The validity test results of the 30 statement items showed values greater than 0.3, and the reliability test indicated instrument values above 0.7, signifying that the instrument is reliable and feasible for use. The results of the moderation regression test show that the Government Accounting Standards significantly influence the quality of village government financial reports, with a p-value < 0.001, indicating significance at the 0.05 level. Human resources do not have a direct influence on quality but serve only as a moderating factor. The p-value of 0.871 indicates a value greater than 0.05, meaning that HR does not moderate the effect of government accounting standards on report quality. Furthermore, the moderation regression results show that internal control does not significantly affect the quality of financial reports, as the p-value of 0.344 exceeds 0.05. Human resources also do not moderate the influence of internal control on the quality of village government financial reports, as indicated by a p-value greater than 0.05.